2008
DOI: 10.1016/j.mri.2007.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Failure to direct detect magnetic field dephasing corresponding to ERP generation

Abstract: AbstractfMRI has become the method of choice for mapping brain activity in human subjects and detects changes in regional blood oxygenation and volume associated with local changes in neuronal activity. While imaging based on blood oxygenation level dependent (BOLD) contrast has good spatial resolution and sensitivity, the hemodynamic signal develops relatively slowly and is only indirectly related to neuronal activity. An alternative approach termed magnetic source MRI (msMRI) is based on the premise that neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
30
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 22 publications
(25 reference statements)
3
30
0
Order By: Relevance
“…The literature contains several reports of positive results (Kamei et al, 1999; Xiong et al, 2003; Bianciardi et al, 2004; Liston et al, 2004; Konn et al, 2004; Petridou et al, 2006; Truong and Song, 2006; Chow et al, 2006a; Chow et al, 2006b; Chow et al, 2007; Chow et al, 2008; Xue et al, 2009) which conflict with reports of negative results (Chu et al, 2004; Parkes et al, 2007; Mandelkow et al, 2007; Tang et al, 2008; Luo et al, 2009; Rodionov et al, 2010; Luo, Jiang & Gao 2011; Huang, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…The literature contains several reports of positive results (Kamei et al, 1999; Xiong et al, 2003; Bianciardi et al, 2004; Liston et al, 2004; Konn et al, 2004; Petridou et al, 2006; Truong and Song, 2006; Chow et al, 2006a; Chow et al, 2006b; Chow et al, 2007; Chow et al, 2008; Xue et al, 2009) which conflict with reports of negative results (Chu et al, 2004; Parkes et al, 2007; Mandelkow et al, 2007; Tang et al, 2008; Luo et al, 2009; Rodionov et al, 2010; Luo, Jiang & Gao 2011; Huang, 2014). …”
Section: Introductionmentioning
confidence: 99%
“…Methods from direct external impedance measurement or from impedance changes related to blood flow (Bagshaw et al 2003) have also been proposed. Methods that rely on perturbations of the main magnetic field have been found to work in small preparations (Petridou et al 2006, Park et al 2006) but in trials performed in bloodless whole brain preparations (Luo et al 2009), and humans in vivo (Chu et al 2004, Tang et al 2008) significant changes have not been found thus far.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, up to date, a consensus has not been reached on the detectability of ncMRI on human subjects. Multiple groups have reported a successful detection of ncMRI signal in human brain (2)(3)(4)(5)(6)(7)(8)(9)(10), while a failure in ncMRI detection has been claimed in other studies (11)(12)(13)(14)(15). Due to these conflicting results, there is still no conclusion on the question whether ncMRI signal is detectable or not.…”
mentioning
confidence: 98%